The Effect of Motivation, Training, and Work Discipline on Soldier Performance at Ajen Kostrad - Diyanna; Suharto; Dhistianti Mei (Indonesian Journal Economic Review (IJER), 2026)
The objective of this study was to determine the influence of motivation, training, and work discipline on the performance of soldiers at the Army Strategic Reserve Command (Ajen Kostrad). This study used a quantitative research method with a descriptive and causal approach. Descriptive research aims to describe the research variables: motivation, training, soldier performance, and work discipline. The population in this study were soldiers at the Army Strategic Reserve Command (Ajen Kostrad) who specifically work in the Army Strategic Reserve Command (Ajen Kostrad). in the music, with amount total 40 person. Soldiers working in The music field has specific tasks and competencies related to the need for motivation, training, and high work discipline to support their performance. The results are in the form of implementation. task military more influenced by compliance to systems, orders, and work discipline; training influential to performance soldier, matter This prove that more and more often orderly activity the training provided will very effective For increase ability soldier in playing music; positive motivation has a significant influence on work discipline, work motivation is able to have a positive impact on the level of work discipline; positive influence training to soldier performance more nature direct, And No depends on role work discipline as mediator.